Relationship between indoor air pollutants exposure and respiratory symptoms among bus drivers in a Malaysian public university - Khairi Anuar, Muhammad Haikal; Jalaludin, Juliana; Suhaimi, Nur Faseeha (Malaysian Public Health Physicians' Association, 2023)
Bus drivers are continuously exposed to air pollutants such as particulate matter while working; hence, they have a high risk for respiratory diseases. This study aimed to investigate the associations of exposure to particulate matter (PM2.5, PM10) and nitrogen dioxide (NO2) inside campus transit buses with respiratory symptoms among bus drivers. A cross-sectional comparative study was conducted among 38 bus drivers as the exposed group and 38 office workers as the comparative group at a Malaysian public university. Indoor air monitoring was performed for 8 hours using SidePak Personal Aerosol Monitor, DustTrak II Aerosol Monitor, and Air Quality Monitor, while background information and self-reported respiratory symptoms were obtained using an adapted American Thoracic Society (ATS-DLD-78-A) questionnaire. Air pollutants (PM2.5, PM10 and NO2) exposure between both groups was significantly different at p<0.05. The exposed group had higher odds of getting cough (OR=2.5), chronic cough (OR=2.2) and chronic phlegm (OR=4.6) than the comparative group. Moreover, there were significant associations between PM10 and PM2.5 concentrations with cough (OR=2.2), chronic cough (OR=2.2), and chronic phlegm (OR=2.2). Meanwhile, only cough was significantly associated with NO2 (OR=2.4). Multiple logistic regression showed that the main predictor for cough was PM2.5 (OR=3.2), for chronic cough was PM10 (OR=5.0), and for chronic phlegm was work duration (OR=1.3). In short, the exposed group was exposed to higher concentrations of air pollutants than the comparative group, leading to a higher prevalence of respiratory symptoms among the bus drivers. These findings provide important evidence for future programs to improve the air quality in buses. It is recommended that the indoor air quality inside the bus should be monitored periodically to ensure the drivers and the passengers are not exposed to air pollutants above the permissible limit.